Motivation and challenges of Community of Sant’egidio (CoS) in providing educational services - Bete, Rufina Nenitriana S.; Ama, Roy Gustaf Tupen (JURNAL SPIRITS, 2024)
There is substantial amount of human scavenger experiencinglimitation to attend formal educations, e.g., limited access to educationor forced to quit at young age to make living. Community of Sant’Egidio(CoS) is a community-based education provider starting in Italy in1968 and branching in Yogyakarta, especially at Kampung PemulungBlok O Yogyakarta (KPBOY). Several challenges faced by CoS, including socially (peers) supported habit of streets living of human scavenger. The aim of this study is to profoundly examine the motivation and challenges faced by CoS in providing educational services at KPBOY.Using qualitative approach, this study employed case study method and purposive sampling. Results showed that in providing educational services, CoS experienced several challenges. However, members of CoS are highly motivated to implement the educational services.